Rebranding of German Bakery, Pune: A Case Study - Srivastava, Mallika; Bhanot, Dhruv; Tamhane, Tarini (Indian Journal of Marketing, 2014)
Recently, after 3 years, the German Bakery reopened its doors to its patrons. Eagerness hovers, but within the lines of prudence and security checks. The 2010 blasts that killed 17 and injured at least 60 people right there creates a certain curiosity to visit the German Bakery. While it was once a humble cafe with communal seating and self-service; the new German Bakery is now a swanky cafe with well informed waiters and an extended menu. It has been rebuilt and restructured to make the emotional people of Pune forget the dark past that it holds. This case study analyzed the current branding strategy of the German Bakery and made a comparison with its pre-existing model, that is, the model followed prior to February 2010. The case study aimed to highlight the concept of rebranding in the context of marketing strategies adopted by the German Bakery, and examined the steps taken by the owners to revamp and safeguard its premises post the 2010 blasts. The case study also took into account the customers’ feedback about the revamped German Bakery, Pune.